Real-World Characterization of Dimethyl Fumarate-Related Gastrointestinal Events in Multiple Sclerosis: Management Strategies to Improve Persistence on Treatment and Patient Outcomes - Min, Jinny (Neurol Ther, 2019)
INTRODUCTION: Delayed-release dimethyl fumarate (DMF) is an effective treatment for multiple sclerosis (MS). Some patients experience gastrointestinal (GI) adverse events (AEs) that may lead to premature DMF discontinuation. This study characterized the impact of site-specific GI management strategies on the occurrence of GI events and discontinuation patterns. METHODS: Data on GI events and DMF persistence were retrospectively abstracted from medical records of patients treated with DMF in routine medical practice in the EFFECT study (NCT02776072). GI management strategies were assessed via a study site questionnaire. Discontinuation rates were analyzed according to counseling patterns. RESULTS: Of 826 DMF-treated patients at 66 sites, 809 from 65 sites were eligible for the GI analysis; of these, 27% experienced GI AEs. Within 1 year of treatment, 14% (118/826) of patients discontinued DMF, 5% (44/809) due to GI events. Most sites (92%) reported that patients were very likely (> 75% of the time) to be counseled about GI events at/before DMF treatment initiation and/or to be recommended that DMF be taken with food (86%); 48% of sites reported to be very likely to recommend using symptomatic therapies for GI AEs. Lower discontinuation rates were reported at sites very likely versus not very likely (≤ 75% of the time) to (1) provide counseling; (2) provide specific details regarding GI events; or (3) recommend taking DMF with food, and/or using symptomatic GI therapies. CONCLUSION: Counseling and other GI management strategies at initiation of DMF treatment appear to reduce the burden of GI events, and a variety of GI management strategies may improve DMF persistence. TRIAL REGISTRATION: NCT02776072. FUNDING: Biogen (Cambridge, MA, USA). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40120-019-0127-2) contains supplementary material, which is available to authorized users.